2001
DOI: 10.1128/cdli.8.5.909-912.2001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemicon SimulFluor Direct Fluorescent Antibody Staining with Cell Culture and Shell Vial Direct Immunoperoxidase Staining for Detection of Herpes Simplex Virus and with Cytospin Direct Immunofluorescence Staining for Detection of Varicella-Zoster Virus

Abstract: A new rapid direct immunofluorescence assay, the SimulFluor direct fluorescent-antibody (DFA) assay, which can simultaneously detect herpes simplex virus types 1 and 2 (HSV-1 and -2) and varicella-zoster virus (VZV), was evaluated in comparison with our current standard procedures of (i) shell vial direct immunoperoxidase (shell vial IP) staining and cell culture for detection of HSV and (ii) cytospin DFA staining for VZV detection. A total of 517 vesicular, oral, genital, and skin lesion specimens were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 8 publications
1
17
0
1
Order By: Relevance
“…1,2 The sensitivity of HSV DFA testing compared with viral culture was only 1 point lower (61%) in our patient population compared with studies conducted on specimens collected from patients where age was not specified (62-95%). [1][2][3][4][5][6][7][8][9] The study is limited primarily by the use of a secondary data source collected during the course of routine clinical care. Since test performance was at the discretion of the treating physicians, there was opportunity for bias by intention.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The sensitivity of HSV DFA testing compared with viral culture was only 1 point lower (61%) in our patient population compared with studies conducted on specimens collected from patients where age was not specified (62-95%). [1][2][3][4][5][6][7][8][9] The study is limited primarily by the use of a secondary data source collected during the course of routine clinical care. Since test performance was at the discretion of the treating physicians, there was opportunity for bias by intention.…”
Section: Discussionmentioning
confidence: 99%
“…Tzanck smear cannot differentiate between HSV and VZV. 101,102 Direct immunofluorescent-antibody staining takes only 3 h to perform 103,104 and the SimulFluor direct immunofluorescent-antibody staining assay only 1.5 h. 105 At present, PCR for VZV DNA is considered the best diagnostic tool because it is very specific and sensitive and can detect viral DNA in vesicle samples, crusts and throat swabs from patients with varicella or HZ.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…4,63 In a study of 32 cutaneous lesions, Solomon et al found Tzanck smears to be positive in 53% of patients. 5,63 Results of both procedures should be available in less than 2 hours if the laboratory is equipped to do these tests. The technique is simple and consists of scraping the edges of the lesion with a scalpel blade, gently touching the scraped material onto a glass slide which is then allowed to air dry.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…A culdocentesis aspirate during this evaluation grew HS in culture. 63,69 According to Velasco, 61 m-c lesions are only found in 40% of patients with herpes hepatitis. M-c lesions were noted in 15 (71%) of them.…”
Section: Are M-c Lesions Present In Patients With Hs Hepatitis?mentioning
confidence: 99%